STUDI PENGARUH UKURAN PIXEL IMAGING PLATE TERHADAP KUALITAS CITRA RADIOGRAF - Ahmad Sudin; Hendri Widyandari; Zaenul Muhlisin (Youngster Physics Journal, 2015)
This study aims to determine the image on each imaging plate which has a different pixel sizes. This research is using a plane X-ray, Computed Radiography (CR) which is used in the diagnostic field. This study uses three imaging plate each having size of 0.097 mm, 0.115 mm and 0.168 mm with stepwedge objects on it and use the same factor, namely kV eksposi: 64.5 and mAs: 16. In each of the imaging plate in eksposi 3 times and the results of each radiograph imaging plate will be measured by using a densitometer. Stepwedge radiograph of the measurement results will be obtained the density and contrast value of each imaging plate. Contrast value for each imaging plate will be compared so they will know what the size of the imaging plate which has a higher contrast value. Research on the effects of different pixel size on the imaging plate is done in Radiology Hospital Tugu Semarang, in July 2014. From the results it can be concluded each different pixel sizes on the imaging plate will generate a different image quality.Keywords: pixel,imaging plate,Quality Preview, contras , density